Impact of Dietary Patterns on Anemia Incidencein Adolescent Girls - Miliana Fantini; Nurlailis Saadah; Astuti Setiyani; Sulikah Sulikah (International Journal of Advanced Health Science and Technology, 2025)
Anemia remains a major public health concern among adolescent girls, as it impairs growth, cognitiveperformance, physical endurance, and overall well-being. In Magetan Regency, anemia prevalence remains high, reaching51.02% in the Tebon Health Center area. Dietary inadequacy is recognized as one of the primary contributors to anemia duringadolescence, a period characterized by rapid growth and increased nutritional demands. This study aimed to analyze the influence of dietary patterns on anemia incidence among adolescent girls at SMP Negeri 1 Barat, Magetan Regency. A cross-sectional observational design was employed, involving 122 female students aged 12–15 years selected through total sampling. Dietary patterns were measured using a validated questionnaire, and hemoglobin levels were assessed using a digital Hb device.Data were analyzed through univariate statistics and the Chi-square test with a significance level of α = 0.05. The findingsindicated that 55.7% of respondents exhibited poor dietary patterns, while 56.6% experienced mild anemia and 12.3% moderateanemia. Among students with good dietary habits, 75% did not experience anemia; conversely, 73.6% of those with poordietary patterns had mild anemia. Statistical testing demonstrated a significant relationship between dietary patterns and anemiaincidence (p = 0.000). These results confirm that inadequate dietary intake substantially contributes to reduced hemoglobinlevels among adolescent girls. Strengthening nutrition education, promoting balanced meals, and enhancing school-basedhealth programs are essential strategies for anemia prevention. Collaboration between health authorities, schools, and youthcounseling groups is recommended to improve dietary behaviors and reduce anemia among adolescents.